2017
DOI: 10.1016/j.ajic.2017.04.003
|View full text |Cite|
|
Sign up to set email alerts
|

Health problems and disinfectant product exposure among staff at a large multispecialty hospital

Abstract: Background Hospital staff expressed health concerns after a surface disinfectant product containing hydrogen peroxide, peracetic acid, and acetic acid was introduced. We sought to determine if this product posed a health hazard. Methods An interviewer-administered questionnaire on work and health characteristics was completed by 163 current staff. Symptoms that improved away from work were considered work-related. Forty-nine air samples were taken for hydrogen peroxide, peracetic acid, and acetic acid. Preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 23 publications
2
51
0
8
Order By: Relevance
“…Few studies have evaluated occupational exposure to HP, PAA, and AA and health outcomes in a health care setting (Cristofari-Marquand et al , 2007; Casey et al , 2017). In this study, work-related acute eye and nasal symptoms and chronic airway symptoms were reported by hospital workers using a sporicidal product containing HP, PAA, and AA.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated occupational exposure to HP, PAA, and AA and health outcomes in a health care setting (Cristofari-Marquand et al , 2007; Casey et al , 2017). In this study, work-related acute eye and nasal symptoms and chronic airway symptoms were reported by hospital workers using a sporicidal product containing HP, PAA, and AA.…”
Section: Discussionmentioning
confidence: 99%
“…A range of discomfort was reported for workers exposed to between 1.0 ppm and 3.0 ppm of this mixed aerosol in this same report. Additional health effects, which have been recently documented, include a possible link to exacerbation of asthma in workers (Casey et al, 2017;Hawley et al, 2017). Given its current Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has been done previously at exposure to most frequently used disinfectant compound, that is, quats, sodium hypochlorite, hydrogen peroxide, alcohol, and glutaraldehyde. All of these were linked with an increased risk of chronic obstructive pulmonary disease (COPD), asthma, and eye irritation on health workers and individuals when used regularly (Casey et al 2017;Dumas et al 2019;Weinmann et al 2019). Chemical residues left on a surface can become airborne and inhaled, and often contribute to poor indoor air quality with consequences for the asthmatic, allergic, or sensitive people (IOM 2000).…”
Section: Toxic Effect Of Disinfectantsmentioning
confidence: 99%